Multi-form multi-function device/wearable - Tay, Keith Zhao Shen (Nanyang Technological University, 2020)
This project aims to develop a device/wearable which provides an innovative way in which a change in shape/function can lead to a change in functionality. The device integrates multiple sensor modules with an on-board microcontroller unit communicating with a Raspberry Pi over a Bluetooth link. This report details the process of developing this device including various considerations when selecting the components, materials used for the strap of the device, form vs function applications and the communication protocols used in the final working prototype. The software portion of this project will be also be further discussed. Microcontroller signals will then be sent to a Raspberry Pi for signal processing and applications can thus be carried out.